Chicken germplasms and their conservation in Bangladesh: A review - Hamid, MA (SAARC Journal of Agriculture, 2019)
The present article addresses the scenario of chicken genetic resources, their production and reproduction performances and their conservation in Bangladesh. The chickens, among other poultry species available in the country, are the most versatile component for meat and egg production. The chicken germplasms available in the country are indigenous, exotic, crossbred, and commercial hybrid. The indigenous chicken population is comprised of Non-descript Desi (ND), Naked Neck (NN), Aseel (AS), Hilly (H), Native Dwarf and Jungle Fowl etc. The exotic chicken such as, White Leghorn (WL), White Rock (WR), White Cornish (WC), Rhode Island Red (RIR), Australorp, Fayoumi, Barred Plymouth Rock (BPR) etc. are imported mostly to upgrade the indigenous stock. The crossbred of different chickens are used in the country in intensive, semi-intensive and scavenging management system. The commercial hybrid such as grandparent stock (GP), parent stock (PS), commercial broiler, commercial layer etc. has got most popularity for meat and egg production in the country. Conservation and improvement program of endangered native chicken such as Aseel and Native Dwarf chicken should be taken both in-situ or ex-situ in vivo by public sector/research institutes/universities. SAARC J. Agri., 17(1): 119-134 (2019)